PENILAIAN TINGKAT KEBANGKRUTAN BANK UMUM SYARIAH DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Muhammad Fikri Hidayat; Mufti Arief Arfiansyah (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
This study analyzes the effect of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operating Expenses Operating Income (BOPO), Debt to Asset Ratio (DAR), and Financing to Deposit Ratio (FDR) on the possibility of financial difficulties in Sharia Commercial Banks, with Company Size as a moderation for the 2020 – 2022 period. The study population included all Sharia Commercial Banks registered with the Financial Services Authority. The research sample consisted of nine Islamic commercial banks, selected using the purposive sampling method. Data analysis was performed using panel data logistic regression analysis and magnetic resonance angiography (MRA Moderated Regression Analysis) using Eviews software version 10. The results showed that the Capital Adequacy Ratio (CAR) and Debt to Asset Ratio (DAR) did not have a significant impact on the risk of possible financial stress. However, Non Performing Financing (NPF) and Operating Expenses Operating Income (BOPO) have a significant positive impact on the risk of possible financial stress. In addition, Company Size moderates the influence of NPF and BOPO, while the Financing to Deposit Ratio (FDR) does not have a significant impact on such risks.